2005
DOI: 10.1055/s-2005-872905
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Levels in Patients with Paget's Disease of Bone

Abstract: A locally accelerated bone turnover is the pathophysiological basis of Paget's disease of bone (PD) and may result in severe bone deformations and pain. Affected bone sites are hypervascularized. Secreted endothelial products such as endothelin-1 (ET-1), influence bone metabolism. We investigated a possible correlation between ET-1 plasma concentrations and bone metabolism in patients with PD and whether ET-1 plasma levels are regulated by i. v. bisphosphonate treatment. Plasma ET-1 levels were determined in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
4
0
3
Order By: Relevance
“…Two studies have found elevated plasma levels of endothelin-1 (ET-1) in PD compared to controls using ET-1 as a marker for angiogenesis [26,27]. In conclusion, our study could demonstrate regional microcirculation in Paget's disease of bone by using dynamic contrastenhanced MRI.…”
Section: Discussionmentioning
confidence: 56%
“…Two studies have found elevated plasma levels of endothelin-1 (ET-1) in PD compared to controls using ET-1 as a marker for angiogenesis [26,27]. In conclusion, our study could demonstrate regional microcirculation in Paget's disease of bone by using dynamic contrastenhanced MRI.…”
Section: Discussionmentioning
confidence: 56%
“…Higher level of endothelin-1 (ET-1) has been reported in PDB patients, suggesting both its phyisopathological role in the disease and the fact that metabolism in the pagetic bone affects endothelial cell metabolism, and maybe also modulated by endothelial cell products [69,70]. Larger studies replicating these findings are needed before considering ET-1 as a possible new useful marker of PDB-related activity.…”
Section: Bone Resorption Markersmentioning
confidence: 93%
“…Arterial calcification in the aorta, iliac, femoral, gluteal and pelvic arteries [70] (cause unknown). (3) Calcification of the aortic valve [88] and the interventricular septum.…”
Section: Cardiovascular Complications Of Paget's Disease Of Bonementioning
confidence: 99%
“…ET-1 induces not only a mitogenic effect, but also an inhibition of OB differentiation (Takuwa et al 1990;Hiruma et al 1998;Kitten et al 1997). Other lines of evidence indicate a physiopathological role of ET-1 in several diseases of human bones, such as Paget's disease (Tarquini et al 1998;Pirzer et al 2005) and prostate-cancerinduced OB metastases (Jimeno and Carducci 2004). Moreover, we have demonstrated, in a human cell line, that the Cx43 level alters the ET-1 effects on OB differentiation (Niger et al 2008), as shown for other modulators such as PTH (Donahue et al 1995;Chung et al 2006).…”
Section: Introductionmentioning
confidence: 96%